MOTIVATION AND OBSTACLES IN MASTERING ARABIC CONVERSATION AMONG STUDENTS OF STEI PERMATA BOJONEGORO: QUALITATIVE STUDY - Siti Imaniatul Muflihatin (Universitas Islam Negeri Sumatera Utara Medan, 2025)
Arabic conversational ability is one of the essential competencies for students at Islamic higher education institutions, particularly in supporting the understanding of Islamic sciences and academic communication. However, in practice, not all students are able to master Arabic speaking skills effectively. This study aims to describe the motivations and obstacles faced by students of STEI Permata Bojonegoro in mastering Arabic conversation. This research employs a qualitative approach with a descriptive research design. The research subjects were students of STEI Permata Bojonegoro who were enrolled in Arabic language courses. Data were collected through in-depth interviews, classroom observation, and documentation. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing.